Surface fitting of an involute spur gear tooth flank roughness measurement to its nominal shape - Brandão, José A. (2016)
A method for fitting a topography measured on an involute spur gear tooth flank to its nominal shape is proposed, so that the exact position along the length of the tooth from which the measured surface originates can be determined, and so that the nominal shape of the surface can be subtracted prior to roughness parameters calculation.